Why are bank runs sometimes partial? - Ilkka Kiema; Esa Jokivuolle (Bank of Finland, 2015)
​Concern that government may not guarantee bank deposits in a future crisis can cause a bank run. The government may break its guarantee during a severe crisis because of time-inconsistent preferences regarding the use of public resources. However, as deposits are with-drawn during the bank run, the size of the government's liability to guarantee the remaining deposits is gradually reduced, which increases the government's incentive to provide the promised guarantee. This in turn reduces depositors' incentive to withdraw, which may explain why bank runs sometimes remain partial. Our model yields an endogenously determined probability and size of a partial bank run. These depend on a common signal as to the future state of the economy, the cost of liquidity provision to banks, and the government's reputational cost of breaking the deposit guarantee. We apply the model to a multi-country deposit insurance scheme, an idea that has been aired in the context of the European Banking Union.
URN:NBN:fi:bof-201504131153
Keywords: G21; G28; 330